Ex vivo pharmacokinetic/pharmacodynamic of hexahydrocolupulone against Clostridium perfringens in broiler chickens - Zhang, Wanying; Lu, Yixing; Ma, Minglang; Yang, Jinyu; Huang, Huiguo; Peng, Xianfeng; Zeng, Zhenling; Zeng, Dongping (Frontiers in Veterinary Science, 2024)
The economic impact of necrotizing enteritis (NE) resulting from Clostridium perfringens infection has been significant within the broiler industry. This study primarily investigated the antibacterial efficacy of hexahydrocolupulone against C. perfringens, and its pharmacokinetics within the ileal contents of broilers. Additionally, a dosing regimen was developed based on the pharmacokinetic/pharmacodynamic (PK/PD) model specific to broilers. Results of the study indicated that the minimum inhibitory concentration (MIC) of hexahydrocolupulone against C. perfringens ranged from 2 mg/L to 16 mg/L in MH broth. However, in ileal content, the MIC ranged from 8 mg/L to 64 mg/L. The mutation prevention concentration (MPC) in the culture medium was found to be 128 mg/L. After oral administration of hexahydrocolupulone at a single dosage of 10-40 mg/kg bodyweight, the peak concentration (Cmax), maximum concentration time (Tmax), and area under the concentration-time curve (AUC) in ileal content of broilers were 291.42-3519.50 µg/g, 1-1.5 h, and 478.99-3121.41 µg•h/g, respectively. By integrating the in vivo PK and ex vivo PD data, the AUC0-24h/MIC values required for achieving bacteriostatic, bactericidal, and bacterial eradication effects were determined to be 36.79, 52.67, and 62.71 h, respectively. A dosage regimen of 32.9 mg/kg at 24-hour intervals for a duration of 3 days would yield therapeutic efficacy in broilers against C. perfringens, provided that the MIC below 4 mg/L.